A Scrum and Blackbox Testing Approach for Smart Air Quality Control Software Development - Alhafis Dicka Dwikumara; Oscar Hadikaryana (Universitas Kebangsaan Republik Indonesia, 2023)
This research reveals the serious challenges faced by Indonesian cities, including Jakarta, Surabaya, and Bandung, regarding indoor air quality. Urbanization and modern lifestyles have exacerbated indoor air pollution, particularly PM and CO2 particles. WHO data confirms the exceeding concentrations of PM and CO2 particles in several urban areas, including office spaces and classrooms. This study explores an Internet of Things (IoT)-based solution utilizing sophisticated sensors to monitor and control indoor air quality. Through this innovative approach, the research tests the hypothesis of the solution's effectiveness by applying blackbox testing and the Scrum method in software development. The research findings demonstrate that the solution effectively controls air quality and provides relevant data for occupants. Its ability to address air quality issues, especially in controlling PM and CO2 particles, shows a positive impact on the urban environment in Indonesia. Air Quality, IoT, advanced sensors, Urban Environment, Blackbox Testing, and Scrum Method form the foundation of this innovative approach, blending technology and software development. Thus, this research not only tackles indoor air quality challenges but also represents a progressive step towards safeguarding the health and comfort of urban residents.